Time and Cost Performance Analysis using the Earned Value Method in the Construction Project of the Dormitory Building at Airlangga University Campus C in Surabaya - Idrus Idrus; Henny Pratiwi Adi; Antonius Antonius (Universitas Islam Sultan Agung, 2025)
Construction projects often face challenges in the form of delays and cost overruns due to discrepancies between plans and actual implementation. The Dormitory Building at Airlangga University Campus C in Surabaya was selected as a case study to comprehensively evaluate project performance. The purpose of this study is to evaluate time and cost performance using the Earned Value Management (EVM) method to provide an accurate picture of the deviations that occur and as a basis for project control recommendations. This study uses a descriptive quantitative approach with secondary data in the form of weekly progress reports, basic schedules, and project financial records. The analysis was conducted through the calculation of EVM indicators, which included Planned Value (PV), Earned Value (EV), Actual Cost (AC), Cost Performance Index (CPI), Schedule Performance Index (SPI), and Estimate at Completion (EAC). The results show that the project experienced delays with an average Schedule Performance Index (SPI) value of 0.92, or approximately 8% behind schedule, while the average Cost Performance Index (CPI) value of 1.05 indicates cost efficiency of 5% compared to the initial budget. The Estimated Cost at Completion (EAC) projects a completion cost of IDR 94.8 billion, which is lower than the contract value of IDR 95.6 billion. Therefore, the project is still under control in terms of cost but requires accelerated work to meet deadlines, while the application of EVM has proven to be effective as an early warning tool and a basis for decision-making in construction project management.